Cost savings through supplier relationship management in indirect procurement in a Finnish MNC - Wang, Lifan (My University, 2025)
This thesis examines how Supplier Relationship Management (SRM) contributes to cost savings in indirect procurement within a multinational corporation (MNC). While SRM has been widely studied in direct procurement, its role in indirect categories is less explored. Indirect procurement is usually characterized by fragmented spend, a large supplier base, and a high proportion of services, which makes traditional cost-reduction approaches less effective. Given these complexities, this study investigates how SRM practices are implemented in indirect procurement and how they support both measurable and long-term cost efficiency. A qualitative case study was conducted using Wärtsilä, a Finnish MNC operating in the marine and energy sectors. Data were collected through semi-structured interviews with procurement professionals, suppliers, and internal stakeholders, complemented by internal company reports. The analysis followed a thematic approach and was guided by the Actors-Resources-Activities (ARA) model. The findings show that SRM contributes to cost savings through three main mechanisms: improved process efficiency, better use of organizational and supplier resources, and stronger relational outcomes. SRM practices are most mature with strategic and leverage suppliers, where spend concentration and business dependence justify deeper collaboration. For routine suppliers, efficiency comes from standardization, automation, and supplier consolidation. Bottleneck suppliers require relationship-based risk mitigation rather than cost-focused negotiations. Trust, transparency, and long-term collaboration are central drivers for sustainable cost benefits, especially where innovation or service improvements influence indirect costs. The study concludes that SRM creates value in indirect procurement not only through price reductions but also by enabling long-term efficiency, reduced complexity, and operational resilience. Its effectiveness depends on structured supplier segmentation, digital enablement, and the relational competence of procurement teams. The results highlight the need for differentiated SRM strategies that reflect supplier roles within indirect spend instead of uniform relationship management across the supplier base.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business